Riesz Inequality for Harmonic Quasiregular Mappings (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we generalize the Riesz theorem for harmonic quasiregular mappings for a special case (when p = 2) in the unit disc. Our results improve similar results in this field and are proved with milder conditions. Moreover, we prove another variant forms of Riesz inequality for harmonic quasiregular functions.
Keywords: Harmonic mappings, Quasiregular mappings, Riesz theorem